2011
DOI: 10.1007/s10750-011-0606-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of live diatoms in bioassessment: a large-scale study of Western US streams

Abstract: Diatom-based stream bioassessment is constantly being improved to meet the increasing demands of water quality management. This study examined whether percentage of live diatoms (PLD) in periphyton communities can be used as a metric of human disturbance in streams and rivers. The analyzed dataset (587 sites) was collected over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…The percentage of live cells tended to decrease downstream, as already reported by Stevenson and Bahls [52] and Gillet et al [53] who examined whether the percentage of live diatoms in periphyton communities could be used as a metric of human disturbance in streams and rivers.…”
Section: Discussionsupporting
confidence: 71%
“…The percentage of live cells tended to decrease downstream, as already reported by Stevenson and Bahls [52] and Gillet et al [53] who examined whether the percentage of live diatoms in periphyton communities could be used as a metric of human disturbance in streams and rivers.…”
Section: Discussionsupporting
confidence: 71%
“…Identification of live preserved material can be particularly difficult and uncertain, but Gillett et al. () found no difference in the ecological inferences from counts of live diatoms (frustules with visible chloroplasts) and cleaned diatoms (acid‐cleaned frustules) from the same sample.…”
Section: Issues In Taxonomy and Relationship To Bioassessmentmentioning
confidence: 99%
“…Gillett et al . () had shown, on streams of Western USA, that classical methods used for bio‐assessment are valuable for the taxonomic precision obtained. They showed that counting performed only on live diatoms offers better ecological reliability; however, they emphasized that the percentage of empty frustules may be used in bio‐assessment methods as a metric for monitoring human disturbance.…”
Section: Discussionmentioning
confidence: 99%